Pengaruh Digital Storytelling di Media Sosial terhadap Minat Berkunjung Generasi Z ke Destinasi Wisata di Daerah Istimewa Yogyakarta - Suwandi, Amanda Kresna Rahayu; Wardhana, Arya Kusuma; Lestari, Dewi (Journal of Tourism Sciences, Technology and Industry, 2025)
Tourism has undergone a significant digital transformation with the rise of social media technology. Digital storytelling has emerged as an effective marketing strategy to attract tourists, particularly Generation Z, who are more responsive to visually driven and interactive narratives. This study aims to analyze the influence of digital storytelling on social media on Generation Z’s visit intention to tourist destinations in the Special Region of Yogyakarta. A quantitative approach was employed using a survey method and purposive sampling technique to collect data from 100 respondents who actively use social media. Inferential statistical analysis was conducted using multiple linear regression, along with classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests. The findings reveal that digital storytelling elements related to visualization and audience engagement significantly influence visit intention. However, not all aspects of storytelling have a direct impact on tourists’ decisions. The implications of this study highlight the importance of using authentic and interactive storytelling to enhance the appeal of tourist destinations. This research provides valuable insights for tourism marketers in designing more effective digital content strategies to attract Generation Z tourists.